2010
DOI: 10.1016/j.humpath.2010.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The epidermal growth factor receptor pathway in relation to pelvic lymph node metastasis and survival in early-stage cervical cancer

Abstract: The epidermal growth factor receptor pathway in relation to pelvic lymph node metastasis and survival in early-stage cervical cancer Eijsink, J.J.; Noordhuis, M.G.; Ten Hoor, K.A.; Kok, M.; Hollema, Harry; de Bock, Gertruida H; Nijman, Hans; Schuuring, Eduardus; Wisman, G.B.A.; van der Zee, Ate Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…There was a positive expression of EGFR correlated with higher grade, high incidence of lymph node metastases, and advanced stage of cancer. These findings are close to that of Eijsink et al [15] who reported that EGFR overexpression was more frequent in advanced cases of CSCC and significantly associated with disease recurrence. The results are also consistent with Li et al [16] who reported that EGFR over-expression was correlated with increased depth of invasion, LN metastasis, and elevated clinical stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was a positive expression of EGFR correlated with higher grade, high incidence of lymph node metastases, and advanced stage of cancer. These findings are close to that of Eijsink et al [15] who reported that EGFR overexpression was more frequent in advanced cases of CSCC and significantly associated with disease recurrence. The results are also consistent with Li et al [16] who reported that EGFR over-expression was correlated with increased depth of invasion, LN metastasis, and elevated clinical stage.…”
Section: Discussionsupporting
confidence: 92%
“…The present study disclosed that PTEN expression was significantly associated with, smaller tumor size, lower stage, lower grade and negative LN as detected by Eijsink et al [15], who disclosed that loss of PTEN expression is associated with pelvic LN metastasis. The absence of expression of this tumor suppressor protein is consistent with tumor progression.The present results are close to Lee et al [22] who detected that PTEN staining was inversely correlated to grade of differentiation and also with tumor stage.…”
Section: Discussionsupporting
confidence: 76%
“…As a membrane protein, Bcl-2 is overexpressed in cervical cancer tissue. It can prevent apoptosis and prolong the cell life cycle by inhibiting Ca 2+ increases in the cell, closing cell nuclear transportation, and acting as an antioxidant (Saitoh et al, 1999;Eijsink et al, 2010). In this study, the expression rate of Bcl-2 in cervical cancer was significantly higher than in the normal cervix, chronic cervicitis, or CIN tissues.…”
Section: Discussionmentioning
confidence: 50%
“…There was no PTEN expression observed in three of 10 and 0 of 10 PTEN methylation-negative and -positive cases, respectively. The preliminary data from the study by Eijsink et al (27) showed the presence of PTEN gene promoter methylation in four of 19 (21%) cases. No PTEN immunostaining was observed in these four PTEN methylation-positive cases.…”
Section: Discussionmentioning
confidence: 94%
“…Any discrepancies between the data of the PTEN methylation from the high and the low rates may be due to the number of evaluated patients and/or the samples with/without the radiotherapy and/or chemotherapy. The patients in the study by Yang et al (18) received radiotherapy and/or chemotherapy, and the study by Eijsink et al (27) only analyzed 19 cases. Furthermore, the present study showed that the PTEN protein expression in the 102 cervical cancer tissue samples was significantly correlated with the FIGO stage and lymph node metastasis (P<0.05).…”
Section: Discussionmentioning
confidence: 99%